The study of antibiotics prescription pattern in pre, intra and post operative period to patients who later developed surgical site infections in a tertiary care centre - Chavhan, Vaibhav B.; Jaju, Jugalkishor B.; Jadhav, Asha D. (International Journal of Research in Medical Sciences, 2026)
Background: AMR has emerged as major public health problem all over world which can be controlled in paying great attention to judicious use of them. In 2012, ICMR started ASP to reduce SSIs by doing right antimicrobial prophylaxis and emphasised to prevent drug resistance. We aimed to see pattern of antibiotics prescribed in pre, intra and post-operative period to patients, who later developed SSIs. Methods: After local IEC-DHR approval, data is collected using retrospective descriptive type study Design. All patients’ medical records who undergone surgeries performed in general surgery, obstetrics-gynaecology, Orthopaedics departments and later developed SSIs in post-operative period are included. Duration of study is 6 months. Only antimicrobials used are recorded and data is analysed using MS Excel. Results: In total 71 case records, females found more. 19-30 years of age patients are more. Antimicrobials of Third generation cephalosporins are used most frequently in Pre, Intra and post-op period. Inj. Ceftriaxone was prescribed more commonly as ‘Monocef’. Half of Antimicrobials are prescribed with Generic names and match DDD recommended by WHO. Average duration of post-operative treatment was 12-13 days. Antibiotics were prescribed till discharge to all. Conclusions: In the study, case records of patients who later developed surgical site infections are studied to know demographic profile. Prescription pattern is most commonly polypharmacy and FDCs were preferred. I.V. was used more than P.O. Treatment modifications are done in 1/4th cases after microbiological reports of swabs of infected sites and this need to be increased.